Etika Profesi dan Pengawasan Hukum Terhadap Penyidik Dalam Proses Penegakan Hukum di Indonesia - Syalsabila, Khairunisa; Lewoleba, Kayus Kayowuan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Ethics and morals are important foundations of running a profession, including the policing profession. In the discharge of investigative duties, investigators as law enforcement agents are demanded to abide by the Police Professional Code of Ethics as guidelines in acting in accordance with the law, upholding humane values, and maintaining the dignity of the institution. The study aims to examine the application of the policing profession’s code of ethics in the investigation process as well as the system of supervision and sanctions applied against investigators who violate legal and ethical procedures of investigation. The method used was a qualitative approach with normative legal research based on library studies. The results of the study show that although ethical rules and guidelines have been established, violations by investigators still occur frequently, which impacts on the decrease of public trust in the institution of policing. It therefore requires a robust system of internal and external oversight as well as the firm and transparent application of sanctions to maintain the professionalism and integrity of the police apparatus in the discharge of its duties